Analisis risiko penyaluran bansos terhadap penerapan good coporate governance pada dinas sosial Kabupaten Rote Ndao - Ledoh, Onimus; M. Ledoh, Farida; S Ledoh, Jizrel E.; Tewu, ML. Deny (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The governance of the distribution of social assistance to the community can lead to social conflict if there is an imbalance. However, this creates many problems that occur in the regions, especially the social service as a sector that handles data improvement. Social assistance governance issues include social assistance data, types of social assistance and social assistance distributors. Research with qualitative methods with case study design. This type of research is participatory and explanatory with data collection techniques, namely survey observations and interviews, as well as document studies. The researcher participatively collected data and information from before 2019 to early April 2022 because the researcher was part of the Social Service of Rote Ndao Regency. Bowtie's analysis technique is used to identify the governance risks of social assistance distribution. The results obtained 11 unwanted events. With this KTD, related to the application of the GCG Tariff principle, measurement and risk assessment is carried out using a heat map, the risk value is obtained from level 10 to 20. Then, opportunity and impact mitigation is carried out so as to reduce the risk level to level 6 to 12. Each KTD has a different impact. different. had a negative impact on the distribution of social assistance and in particular greatly affected GCG. To improve the risk management culture for the distribution of social assistance, the mitigation that has been carried out so far by applying the GCG Tariff principle needs to be further enhanced into an organizational culture.